Structural and properties of nanocrystalline WO3/TiO2-based humidity sensors elements prepared by high energy activation - Rocha, K. O.; Zanetti, S. M. [UNESP] (Elsevier B.V. Sa, 2011)
Nanocrystalline WO3/TiO2-based powders have been prepared by the high energy activation method with WO3 concentration ranging from 1 to 10 molt The samples were thermal treated in a microwave oven at 600 C for 20 min and their structural and micro-structural characteristics were evaluated by X-ray diffraction, Raman spectroscopy, EXAFS measurements at the Ti K-edge, and transmission electron microscopy. Nitrogen adsorption isotherms and H-2 Temperature Programmed Reduction were also carried out for physical characterization. The crystallite and particle mean sizes ranged from 30 to 40 nm and from 100 to 190 nm, respectively. Good sensor response was obtained for samples with at least 5 mol% WO3 activated for at least 80 min. Ceramics heat-treated in microwave oven for 20 min have shown similar sensor response as those prepared in conventional oven for 120 min, which is highly cost effective. These results indicate that WO3/TiO2 ceramics can be used as a humidity sensor element. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: WO3/TiO2; High energy activation; Humidity sensor; Nanostructured oxide